Trabalho e política pública: subsídios para uma avaliação das políticas de turismo a partir do estudo dos trabalhadores informais da Praia do Futuro em Fortaleza – CE - Silva, Ivo Luis Oliveira (2008)
This study provides subsidies for the construction of a systematic evaluation of public policies for tourism, considering the change in work in the contemporary world. For this, the research focuses on the evaluation of government policies in the segment of tourism in the city of Fortaleza, from two points. The first is the historical construction of public policies for tourism in the town of Praia do Futuro. The second shows a search to recognize the informal workers of the Praia do Futuro. The hypothesis of this work is that the tourist activity is focused more to the commodification of place, acuada the process of turistificação of space, subject to the interests of capital and the neoliberal policies to the detriment of development itself in order to promote the common welfare. The trailer of this process of turistificação is the effect of the precariousness of work as a crisis of transformation inherent in capitalist production process. The challenge is to analyze the tourism in another aspect, a dimension of all. Efforts are to understand how the informal survive as conforms, and the resistance to social and economic situation on them. Express themselves in their world views, their aspirations in establishing their networks sociabilizarão, building new alternatives in the organization of social life. Thus, it is considered that public policies for tourism can be reduced inequality generated by the market and ensure a minimum of welfare for all. But alone, these policies take character to promote salvation, disguised in speeches votes. Remains how public policies reflect these principles of tourism.